The Hudsucker proxy [videorecording (DVD)] - Coen, Joel; Coen, Joel; Coen, Ethan; Coen, Ethan; Raimi, Sam; Robbins, Tim, 1958-; Leigh, Jennifer Jason, 1962-; Newman, Paul, 1925-2008; Durning, Charles, 1923-2012; True-Frost, Jim; Mahoney, John, 1940-2018 (Warner Home Video, 1999)
When Waring Hudsucker, head of a successful company commits suicide, the board of directors has a plan to make a lot of money, so they decide to appoint a moron to run the company. Mailroom clerk Norville Barnes is exactly what Hudsucker is looking for to be president. They hope that as soon as the stock falls low enough, the director and his friends will buy them up cheaply, take over the company and they will be successful again. However, a tough reporter is suspicious and decides to investigate Hudsucker.